Production of mutants of Gaeumannomyces graminis var. tritici and var. avenae by 4- nitroquinolene-oxide treatment of protoplasts. - P. Bowyer; R. Musker; A. E. Osbourn; B. Clarke; C. Caten; M. J. Daniels (Fungal Genetics Reports, 1992)
The ascomycete fungus Gaeumannomyces graminis is the causative agent of take-all disease of cereals. Much information about the physiology and pathology of this organism has been generated (Asher and Shipton (Eds.) "Biology and Control of Take-All", Academic Press, 1981), but genetic studies such as the production of mutants have been hindered by problems in obtaining viable propagules suitable for mutagenesis (Blanch et al. 1981. Trans. Brit. Mycol. Soc. 77:391-399). The fungus is homothallic but many strains cannot be induced to form perithecia in culture and even the fertile strains produce insufficient numbers of ascospores for use in mutagenesis. It is, however, possible to produce and regenerate large numbers of protoplasts and Rochefrette et al.